Keterkaitan While Collar Crime dengan Coorporate Crime - Deamonika Deamonika; Nur Annisa (BADAN PENERBIT STIEPARI PRESS, 2024)
White collar crime is a crime committed by respected people, while corporate crime is a crime related to corporations. White collar crime and crinre corporations have also always been linked to the crime economy. White collar crime can be controlled by corporations, therefore a type of crime arises, namely corporate services. The research method is literature study, the aim is to find out what forms of crime are categorized as